David Bohm, sua estada no Brasil e a teoria quântica - Freire Jr., Olival; Paty, Michel; Barros, Alberto Luiz da Rocha (Estudos Avançados, 1994)
When the paper A Suggested interpretation of the quantum theory in terms of "hidden" variables, by David Bohm, was published he has been in Brazil at University of São Paulo. He was hit by the McCarthysm, lost his post at the Princeton University and by this he came to the Brazil, where he stayed from 1951 (October) to 1955 (January). We analysed his activity in this period, including his interpretation of the quantum theory and its reception in the scientific community. We pointed out that notwithstanding the adverse conditions, the Brazilian society was able to recept the political persecuted scientist and citizen and to warrant the continuity of his scientific work. The Brazilian science was very benefited by the teaching, the research and the permanent preoccupation with the foundations of physics, features of David Bohm's work.